2005
DOI: 10.5694/j.1326-5377.2005.tb07032.x
|View full text |Cite
|
Sign up to set email alerts
|

Problem‐based learning: a dissemination success story?

Abstract: The demand to implement clinical and educational strategies based on evidence has increased in the past two decades. Over a similar time frame, the problem‐based learning (PBL) approach has been widely adopted by undergraduate medical schools, in spite of empirical reviews suggesting that its effectiveness may be limited. Students claim that PBL provides a more satisfying learning experience than traditional methods. While such an outcome is desirable, it is substantively less than the original promise of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…Examples of measured qualities include competence and understanding of basic and clinical sciences [11]. The present study has shown that the PBL curriculum is effective in improving the attitudes of medical students towards health research.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Examples of measured qualities include competence and understanding of basic and clinical sciences [11]. The present study has shown that the PBL curriculum is effective in improving the attitudes of medical students towards health research.…”
Section: Discussionmentioning
confidence: 61%
“…The demand to implement clinical and educational strategies based on evidence has increased in the past two decades [11]. This is especially true for the PBL curriculum because of its rapid adoption and popularity.…”
Section: Introductionmentioning
confidence: 99%
“…2 In 2006, a new milestone was reached with the establishment of a doctoral program in health sciences at the University of Pécs. Canadian experts also provided valuable support in introducing health technology assessment.…”
mentioning
confidence: 99%
“…To the Editor : The article by Sanson‐Fisher and Lynagh on problem‐based learning (PBL) 1 is very timely, raising important questions about the popularity and efficacy of this method.…”
mentioning
confidence: 99%